Applications of stem cell biology to oculoplastic surgery. Issue 5 (September 2016) - Daniel, Michael G.; Wu, Albert Y.
Abstract : Purpose of review: The review examines the utility of stem cell biology in ophthalmology and oculoplastic surgery. Recent findings: The applicability of stem cell biology varies across a range of different subfields within ophthalmology and oculoplastic surgery. Resident stem cells have been identified in the lacrimal gland, corneal limbus, orbital fat, and muscles of the eye, and can potentially be applied for in-vitro cell and organ cultures with the intent of disease modeling and transplants. The discovery of adipocyte-derived stem cells offered a potentially powerful tool for a variety of oculoplastic applications, such as wound healing, skin rejuvenation, and burn therapeutics. Several groups are currently identifying new uses for stem cells in oculoplastic surgery. Summary: The need for stem cell treatment spans a wide array of subfields within ophthalmology, ranging from reconstruction of the eyelid to the generation of artificial lacrimal glands and oncological therapeutics. The advent of induced pluripotent stem cells opened the realm of regenerative medicine, making the modeling of patient-specific diseases a possibility. The identification and characterization of endogenous stem cell populations in the eye makes it possible to obtain specific tissues through induced pluripotent stem cells differentiation, permitting their use in transplants for oculoplastic surgery.